Study on the factors affecting the level of brand awareness of Hong Duc Pennywort tea bags by customers in Thanh Hoa Province - Cuong, Le Van; Ngoc, Pham Thi; Lan, Le Thi (International Journal of Economics, Business and Management Studies, 2024)
This study aims to determine and evaluate the influence of factors on the level of awareness of the Hong Duc tea bag brand. The authors used the random sampling method from customers visiting the startup market at Hong Duc University. 400 surveys were distributed and 358 valid questionnaires were collected for analysis. Data obtained through the survey were cleaned, coded and analyzed using SPSS 22.0 software. Cronbach alpha reliability coefficients, rotated factor matrices (EFA), and multivariate regression analyzes were performed. The results show that brand image, product quality, promotional activities, perceived price and distribution activities all have a positive impact on the level of brand awareness of Hong Duc pennywort tea bags; in which brand image and products have the greatest influence while distribution activities have the smallest influence on awareness of the Hong Duc Penneywort tea bag brand. These findings are essential to help Hong Duc tea bag brand managers develop appropriate strategies to raise customer awareness of the Hong Duc pennywort tea brand such as improving product quality, strengthen marketing activities to promote images, and establish appropriate promotion strategies, pricing policies and distribution activities; thereby improving the competitiveness of Hong Duc pennywort tea bag brand in the market.